PERBANDINGAN RANCANGAN CAMPURAN BETON ANTARA METODE DoE DAN ACI - Arifal Hidayat (Universitas Pasir Pengaraian, 2012)
Concrete mix designed to determine the composition of the concrete materials. Basically the concrete mix design is intended to produce a composition with a minimum use of materials with a fixed maximum force to consider the standard criteria of the quality of concrete and economical when viewed from the aspect of the overall cost. The purpose of this study was to compare the results of the design (theoretically) a mixture of concrete plans fc '22.5 MPa for 1 m3 using the Department of Environment (DoE) and the methods of the American Concrete Institute (ACI), of both methods is theoretically known to use materials optimal material (economic).Stages in the concrete mix design fc '22.5 MPa were: (1) sieving fine aggregate and coarse aggregate, (2) examination of specific gravity and absorption of fine aggregate and coarse aggregate, (3) examination of the contents of an aggregate weight and (4) examination mud content by using the same material that is aggregated from the Tanjung Belit quary Rokan Hulu regency.